Understanding intra-vaginal and labia minora elongation practices among women heads-of-households in Zambézia Province, Mozambique. Issue 5 (4th May 2017) - Audet, Carolyn M.; Blevins, Meridith; Cherry, Charlotte Buehler; González-Calvo, Lazaro; Green, Ann F.; Moon, Troy D.
Abstract: Intra-vaginal drying and tightening and labia minora elongation are commonly practised in some parts of southern Africa. We sought to capture data on these practices among women living in Zambézia province, Mozambique. Information was gathered from 3543 female heads of household on > 500 variables, including vaginal practices, in 2014. Women who planned to use intra-vaginal tightening substances had 1.84 times higher odds of ever receiving an HIV test ( p < 0.001) and 1.40 times higher odds of at least one antenatal care visit attended during last pregnancy ( p = 0.015). Women who had or planned to undergo labia minora elongation had 2.61 times higher odds of receiving an HIV test in the past ( p < 0.001) and 1.60 times higher odds of attending at least one antenatal care visit during their last pregnancy ( p < 0.001). There was little evidence for a relationship between self-reported HIV status and anticipated use of intra-vaginal tightening substances ( p = 0.21). Current or anticipated participation in labia elongation showed a protective effect on HIV infection ( p = 0.028). Given documented associations between intra-vaginal substance use, vaginal infections and HIV acquisition, understanding the prevalence of vaginal practices is an essential component to addressing the epidemic.